Certificated and Uncertificated Junior High School Teachers in Pulau Burung Subdistrict in 2017/2018 - Leny Wulandari; Almasdi Syahza; Suarman Suarman (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
Teachers are educating leaders in the class. They need to have professional and pedagogy competence in order to make learning process effectively in class. This research was done to know the differences between teacher professional competence and teacher pedagogy competence which certificated or uncertificated on learning process that has been done.This research has been done in November-March 2018. The sample was all teachers in SMP Kecamatan Pulau Burung which are 84 teachers. The data was collected by using differencial scale questionare to test the competences. The data analisys technique is descriptive and Independent sampel T-Test. The research findinfa are:1) after doing the T-Test, there is a significant difference on certificated teacher pedagogy: (a) certificated teacher pedagogy competence has got the higher score toward the indicator of doing educated and dialog learning (80,54%). (b) The lowest score is at the indicator of the used of learning (60,54%). (c) Uncertificated teacher pedagogy competence has got the higher score at the sub competence or educated learning (77,02%). (d) For the lowest score is at the indicator of the use of learning technology(46,80%).2) Uncertificated teacher professional competence, after taking the T-Test, showed that there is not any difference between certificated and uncertificated teacher. (a) Certificated teacher has got the higher score at the indicator of understanding and implementing learning theory to the right level of students attitude development (81,08%). (b) it got the lowest score at the indicator of the ability to use ani kind of facilities, medias, and other learning sources effectively (57,37%). (c) Uncertificated teacher professional competence has got the highest score at the indicator of the ability to create students personality (80,45%). (d) and the lowest score is (57,44%) at the indicator of implementinf the right learninf method.